CAVITATIONAL TREATMENT OF OIL DIESEL FRACTION - V. B. Terentyeva; А. I. Nikolaev; B. V. Peshnev; N. А. Kon’Kova (Тонкие химические технологии)
The results of investigation on the effect of mechanochemical treatment of the diesel fraction on its physicochemical characteristics are presented. Mechanochemical treatment of the diesel fraction was achieved by creating a cavitation effect in the hydrodynamic regime. The studies were carried out in the range of pressure gradients up to 50 MPa, the number of treatment cycles varied from 1 to 5, the temperature of raw material at the apparatus inlet was 0 0С. It is shown that the effect of cavitation is manifested not only in the processing of high-boiling hydrocarbons, but also in a middle distillate directions. So, as a result of the cavitation effect, the density of the diesel fraction and its pour point decrease, and the fractional composition changes. It is suggested that these changes are associated with hydrocarbon degradation. The collapse of gas bubbles leads to a local increase in the temperature of the medium to 800 0C, which, in turn, leads to the destruction of hydrocarbons. Increasing the pressure gradient of the hydrodynamic flow enhances the noted effect. Increasing the number of treatment cycles reduces the effect achieved. A possible reason is the destruction of hydrocarbons formed in the first stage of processing and the formation of polycyclic and aromatic structures. The results presented in the article extend ideas about cavitation regularities in the hydrocarbon environment